Survei Tingkat Skill Related Fitness Pada Siswa-Siswi Sekolah Dasar Negeri Gugus 6-10 Fase C Di Kecamatan Sukun Kota Malang - Romdlon, Auli Fahmi Nadhifatur; Wiguno, Lokananta Teguh Hari (Inspirasi Dunia: Jurnal Riset Pendidikan dan Bahasa, 2024)
The purpose of this study was to determine the level of physical fitness of students in public elementary schools in cluster 6-10 phase c in Sukun District, Malang City. This research is a survey research, using quantitative descriptive methods, the instrument used in collecting data is the Indonesian Student Fitness Test (TKSI). The study sample involved 95 public primary school students of cluster 6-10 phase c in Sukun District, Malang City. The results of the study showed that the 95 students of public primary schools of cluster 6-10 phase c in Sukun District, Malang City as a whole showed that the 40 Meter Run Test was dominated by the “Very Poor” category with 58 (fifty-eight) frequencies. The 8x10 Meter Shuttle Run Test is dominated by the “Excellent” category with 37 (thirty-seven) frequencies. Child Ball Test is dominated by the “Excellent” category with 44 (forty-four) frequencies. Dynamic Balance Test was dominated by the “Good” category with 53 (fifty-three) frequencies. Vertical Jump Test was dominated by the “Moderate” category with 42 (forty-two) frequencies. Hand Touch Reaction Test is dominated by the “Poor” category with 34 (thirty-four) frequencies. With this, the researcher hopes that public elementary schools in cluster 6-10 in Sukun District, Malang City will pay more attention and try to increase the overall level of physical fitness of students.